Automotive lightweight engineering: a method for identifying lazy parts. (1st January 2013) - Caldwell, Benjamin W.; Namouz, Essam Z.; Richardson, Jenkins L.; Sen, Chiradeep; Rotenburg, Thomas; Mocko, Gregory M.; Summers, Joshua D.; Obieglo, Andreas
This paper presents a method for evaluating the lightweightedness of a vehicle, specifically addressing those components whose primary purpose is to aid in manufacturing and assembly rather than to provide end-user function. Seven laziness indicators are described. These indicators are used to evaluate individual vehicle components to aid in identifying mass reduction potential and focus the attention of designers on components or assemblies with high potential for mass reduction. This method is applied to a complete automotive vehicle, demonstrating a mass savings potential of the overall vehicle of approximately 5% of the total mass of the vehicle.